Esquema de análisis de la calidad de la información contable (2019)
The intention of this article is to present a scheme that allows analyzing the impact of the mandatory adoption of International Financial Reporting Standards (IFRS) on the improvement of the quality of accounting information in Colombia. In order to achieve this, a bibliographic review was first carried out, in order to discuss the concepts and their evolution from the branches of organizational management, characteristics and model of accounting normative regulation applicable in Colombia and the qualitative attributes of financial information. Later on, the proposal is presented and finally, the way to approach the reliability and validity analysis of the proposal is established taking into account the descriptive and infe-rential statistics.